Computer Communications: Government Regulation - Herbert E. Marks; Stephen R. Bell (Washington University Law Quarterly, 1977)
As the sole suppliers of telephone or telegraph services, certain carriers have the market power to tie or compel the purchase of their data processing services; they can subsidize the cost of their data processing services with the revenue derived from their monopoly; and they are able to divert resources needed to provide basic telecommunications services to promote their competitive data processing business. The issues raised by such competition will ultimately affect the services and facilities available to all users of computers and communications components needed to link the computer to the user. In this Article, Herbert E. Marks and Stephen R. Bell maintain that the present federal regulatory scheme is unsatisfactory because the areas within which the computer and communications industries may permissibly operate are not clearly defined. As a result, there is considerable overlap and competition. Congress and the FCC in its Second Computer Inquiry are presently considering new methods of regulation.